Investigation of the Reasons Behind Preferring Faculty of Dentistry Atatürk University Among the Enrolled Students - Derya Aslan; Oğuzhan Sari; Alper Özdoğan (Atatürk University, 2024)
Objective: To evaluate the reasons behind choosing Atatürk University Faculty of Dentistry among the enrolled students in the academic terms of 2019-2020 and 2020-2021. Methods: The study was conducted by survey data collection method. The surveys were applied to a total of 202 students whom are enrolled in the faculty of dentistry for 2019-2020 academic year and a total of 168 students for 2020-2021 academic year. Descriptive, frequency analysis, and cross tables were used in statistical analysis of the data obtained. Results: As a result of the analysis, it was found that the preference order of Atatürk University Faculty of Dentistry was 8.6 ± 5.5 for the students of the 2019-2020 academic term and 9.7 ± 6.1 for the students of the 2020-2021 academic term. Conclusion: As a result of the answers to the questionnaire questions, it was found that the students whom are enrolled in our faculty in both terms preferred the dentistry profession and our faculty with prior knowledge, and that the pandemic period did not have a significant effect on their preferences such as profession, city, university. Keywords: Choice of profession, Covid-19, Dentistry, Education Atatürk Üniversitesi Diş Hekimliği Fakültesini Kazanan Öğrencilerin Meslek ve Fakülte Tercih Nedenlerinin İncelenmesi ÖZ Amaç: Bu çalışmada, Atatürk Üniversitesi Diş Hekimliği Fakültesi'ni 2019-2020 ve 2020-2021 akademik dönemlerinde kazanan öğrencilerin meslek ve fakülte tercih nedenlerinin değerlendirilmesi amaçlandı. Yöntemler: Çalışma anket ile veri toplama yöntemi ile gerçekleştirildi. Anketler 2019-2020 akademik döneminde diş hekimliği fakültesini kazanan toplam 202 öğrenciye, 2020-2021 akademik döneminde ise toplam 168 öğrenciye uygulandı. Elde edilen verilerin istatistiksel analizinde deskriptif, frekans analizi ve çapraz tablolardan yararlanıldı. Bulgular: Yapılan analizler sonucunda Atatürk Üniversitesi Diş Hekimliği Fakültesi'nin tercih sıralamasının 2019-2020 akademik dönem öğrencileri için 8.6±5.5, 2020-2021 akademik dönem öğrencileri için ise 9.7 ±6.1 olduğu görüldü. Sonuç: Anket sorularına verilen cevaplar neticesinde her iki dönemde de fakültemizi kazanan öğrencilerin diş hekimliği mesleğini ve fakültemizi önceden bilgi sahibi olarak tercih ettikleri; pandemi döneminin meslek, şehir, üniversite gibi tercihler üzerinde önemli bir etkisinin olmadığı sonucuna varıldı. Anahtar Kelimeler : Covid-19, Diş hekimliği, Meslek seçimi, Öğrenci